The effect of religion on earnings management and capital structure : evidence from Muslim and non-Muslim managed firms in Malaysia : a thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Philosophy in the School of Accountancy, College of Business, Massey University - Muthalib, Unvar Rahman bin Abdul (Massey University, 2002)
This study examines the effect of religion on the earnings management practices and capital structure of Malaysian firms. While prior studies have been useful in identifying economic factors affecting earnings management and capital structure decisions, the prior research has ignored cultural factors generally and religion specifically. My study attempts to augment this research by investigating whether religion, a non-economic motive, has any influence on management decisions related to earnings management and capital structure. In particular, I contrast the behaviour of Muslim and non-Muslim managers in Malaysia. Because Islam discourages interest-bearing debts, I first hypothesise that Muslim managed firms use less interest-bearing debts and preference shares relative to straight equity than the non-Muslim managed firms. Using a sample of 1607 firm-year observations over the period 1987-1998 and a series of univariate and multivariate analyses, I find that the firms' capital structure decisions are not influenced by the religious orientation of their managers. This suggests that Muslim managers and non-Muslim managers behave alike when making capital financing decisions. While this is contrary to expectations, a possible reason for this finding is that Islamic debt instruments were only available after 1991, and Muslim managed firms that had already issued ordinary debt capital were not able to switch to Islamic debt within the timeframe covered by the study. Another possible reason is that Muslim managers do not adhere strictly to the teachings of Islam and are influenced by the Western economic system. Second, I establish the argument that Islam prohibits earnings management practices and hypothesise that Muslim managed firms are less likely to manage earnings than their non-Muslim counterparts. I analyse the data from 170 Malaysian firms listed on the KLSE since 1980 using four common earnings management detecting models, i.e., the Healy, DeAngelo, Jones, and Modified Jones models. The results of the univariate and multivariate analysis are mixed. Tests using the Healy model provide some support for the earnings management hypothesis while the others do not. However, on balance, I conclude that religion does not affect the earnings management practices of Malaysian firms.
Keywords: Business and religion; Management and religion; Muslim businesses; Fields of Research::350000 Commerce, Management, Tourism and Services::350200 Business and Management